Restoration, soil organisms, and soil processes: emerging approaches. (5th September 2020) - Farrell, Hannah L.; Léger, Ariel; Breed, Martin F.; Gornish, Elise S.
Abstract : Better understanding of the connection between aboveground plant communities and belowground soil organisms and processes has led to an explosion in recent research on the applications of this link to the field of ecological restoration. Research is only beginning to have the capacity to link soil organisms and specific ecosystem functions. Establishing general ecological principles of the role microbial communities have during ecological restoration is also still in its infancy. As such, the literature is at a critical point to generate a Special Feature that brings together novel approaches of linking soil and restoration to promote more regular inclusion and consideration of soil organisms and soil‐based processes in ecological restoration. In this special feature, we bring together nine research articles from different ecosystems that study the relationship between restoration activities, soil microbial communities, and soil properties. From these research articles, we describe two primary themes: (1) research on the impacts of ecosystem‐specific restoration activities on soil organisms and processes and (2) research testing methods of soil manipulation to improve restoration outcomes. We hope to inspire readers and restoration practitioners to consider soil microbes and soil processes in their research, restoration projects, and world views.